Development of seating pressure ulcer prevention training system for individual with spinal cord injury / Hartini Hazmi - Hartini , Hazmi (2014)
Pressure ulcer is a serious problem and complication for spinal cord injury (SCI) patients. There are various methods to prevent pressure ulcer which are good quality of cushion and perform pressure relief activity. This study aims to develop a device that can give alert to patients especially SCI to perform pressure relief activity such as push up. Patients need to have the capability and strength at upper body to perform this activity. The design consists of two elements to make the system successful which are sensor and control system. Light dependent resistor (LDR) was used as sensing element to trigger the control system that consists of buzzer and timer to alert the patients. Seven SCI subjects were involved to get the feedback regarding design specification and overall system application. Result from subject evaluation, device successfully alert patients to perform pressure relief activity after 15 minute. With pressure alert system, this device can help patient to cultivate pressure relief activity which can be an effective way to prevent pressure ulcer.